Implementation Of Clinical Pathway For Management Of Copd Exacerbation - Alvin Kosasih (Indonesian Society of Respirology (ISR), 2021)
Background: The effectiveness for reducing the length of stay and produce better outcomes has been applied with the use of the clinical pathway. In this study, we observe the implementation of clinical pathways (CP) and evaluate their effectiveness in the management of Chronic Obstructive Pulmonary Diseases (COPD) exacerbation in Goenawan Partowidigdo Pulmonary Hospital (RSPG) Cisarua Bogor. Method: This research is a quantitative study with an analytical survey method and cross-sectional design. Data collection was carried out by studying documentation on 304 medical record files from early 2019 to July 2020 and clinical pathway forms. Results: There were differences in clinical outcomes before and after the implementation of CP. The difference in the overall mean length of stay (LOS) using CP were 4 days while the who did not use CP were 6 days. For In-Hospital Mortality (IHM) there was 1 death in the CP group, and there were no deaths in non-CP groups. As for the Readmission Rate (RR), the results of the study showed that the most RR was in the CP group, which were 6 patients (54.5%) in 1st wards, 5 patients (62.5 %) in 2nd wards and 39 patients (70.9%) in 3rd wards. These RR results showed that CP of COPD exacerbation must be evaluated further. The average total hospital rate showed a significant difference between the two clinical methods. The hospital rate variable had a very significant difference between the CP and non-CP methods, with a significant value of = 0.0001. Conclusion: The application of CP can reduce the length of stay (LOS) and the average total hospital rate of patients who are hospitalized for COPD exacerbation. This CP must be evaluated further to reduce the readmission.